MAP4K3 regulates body size and metabolism in Drosophila. - Bryk, B.; Hahn, K.; Cohen, S.M.; Teleman, A.A. (Developmental Biology, 2010)
The TOR pathway mediates nutrient-responsive regulation of cell growth and metabolism in animals. TOR Complex 1 activity depends, amongst other things, on amino acid availability. MAP4K3 was recently implicated in amino-acid signaling in cell culture. We report here the physiological characterization of MAP4K3 mutant flies. Flies lacking MAP4K3 have reduced TORC1 activity detected by phosphorylation of S6K and 4EBP. Furthermore MAP4K3 mutants display phenotypes characteristic of low TORC1 activity and low nutrient availability, such as reduced growth rate, small body size, and low lipid reserves. The differences between control and MAP4K3 mutant animals diminish when animals are reared in low-nutrient conditions, suggesting that the ability of TOR to sense amino acids is most important when nutrients are abundant. Lastly, we show physical interaction between MAP4K3 and the Rag GTPases raising the possibility they might be acting in one signaling pathway.